Modification of graphene oxide and graphene oxide–TiO2 solutions by pulsed laser irradiation for dye removal from water. (February 2016) - Filice, S.; D'Angelo, D.; Spanò, S.F.; Compagnini, G.; Sinatra, M.; D'Urso, L.; Fazio, E.; Privitera, V.; Scalese, S.
Abstract: Pulsed laser with visible wavelength (532 nm) allows to modify the properties of graphene oxide (GO) sheets dispersed in water by finely tuning the amount of oxygen functionalities and, therefore, the degree of reduction. In this way both the hydrophilicity and the spectroscopic features of the GO suspension can be changed. This work reports the preparation of reduced graphene oxide (rGO) and mixed solutions of GO or rGO and Degussa P25 ® titania nanoparticles by pulsed laser irradiation. The produced materials are characterized by scanning electron microscopy, Raman spectroscopy and X-ray photoelectron spectroscopy. Their ability to remove methylene blue from water is investigated by studying the dye decolorization.